Investigating the Higher Education Students' Perception of an Interactive Virtual Processing Station Application - Maryadi, Totok Heru Tri; Badarudin, Rohjai; Bintoro, Kukuh (International Journal of Artificial Intelligence Research, 2024)
This study aims to evaluate the Virtual Processing Station as a simulation-based learning medium in the context of engineering education, based on student perceptions. Student perceptions of this medium were evaluated based on four main aspects: relevance, attention, interest, and usefulness. This study involved 30 students from the Department of Electrical Engineering Education at Yogyakarta State University who had used the Virtual Processing Station in laboratory practice sessions. Data were collected through a questionnaire with 17 statements using a Likert scale and supplemented with qualitative feedback from respondents. The results showed that this learning medium was very well received by students, with an average rating of 90.59%. The relevance aspect received the highest score (92.92%), followed by the interest aspect (90.83%) and usefulness (90.56%). Although the attention aspect received a slightly lower score (84.72%), the medium was still considered quite effective in capturing students' attention during the learning process. Positive comments from respondents emphasized the effectiveness of this medium in helping students understand both the practical and theoretical concepts of PLC-based industrial automation systems. The conclusion of this study indicates that the Virtual Processing Station has great potential in supporting more interactive and efficient engineering learning. However, there is still room for improvement in areas such as the user interface and visualization. Future research should focus on assessing the short-term and long-term impacts of this medium, particularly through larger sample sizes and objective assessments of student performance before and after using the Virtual Processing Station. This approach will provide deeper insights into how these medium influences learning outcomes and the development of practical skills in engineering education.